Children, health and well-being : policy debates and lived experience - Brady, Geraldine M.; Lowe, Pam; Olin-Lauritzen, Sonja; Ohio Library and Information Network (Hoboken : Wiley-Blackwell, 2015)
"The book furthers theoretical understandings of the sociology of children's health and illness and encourages productive debate amongst a wide audience, including academics, policy makers, and health-care professionals"--
Includes bibliographical references and index
Keywords: Child welfare; Children -- Health and hygiene; Child health services; Electronic books